Examining cultural relevancy in the ""Doctor Bird Readers"": Text analysis from the perspective of Jamaican children - Headlam, Alis L.
This paper reports on a study that examined whether cultural relevancy was achieved in the development of stories for the "Doctor Bird Readers" by the Jamaican government, for children in Grades 4 through 6, by using Jamaican authors and artists. Quantitative questionnaires were used to survey the schools, and participant observations and informal interviews during the ethnography provided a means of gathering background knowledge of the Jamaican culture. Individual interviews (three 1-hour sessions) were conducted by grade level with four-six students of mixed abilities. Three hundred and fifty-one questionnaires were completed, with results indicating that the books were used daily or frequently. Qualitative interviews revealed that 60 of the 75 stories were considered relevant by the students. The relevancy described by the children in these interviews was both personal and cultural. Background knowledge and experiences that the children brought to the text, combined with their ability to predict what was happening, affected readability the most. Teachers reported that although the books were effective with the middle reading groups, overall the books were having a positive effect on all of the students
Keywords: Doctor Bird readers